Reduction in amyloid β deposition on (18)F-florbetapir positron emission tomography with correction of cerebral hypoperfusion after endarterectomy for carotid stenosis - Ogasawara, Kuniaki (Am J Nucl Med Mol Imaging, 2019)
The process of amyloid β (Aβ) deposition in sporadic Alzheimer’s disease remains unclear. However, hypoperfusion due to vascular pathology may precede Aβ deposition, as suggested by data from animal models and autopsy tissue from Alzheimer’s disease patients. In this exploratory study, we examined the hypotheses that chronic cerebral hypoperfusion due to severe atherosclerotic stenosis of the internal carotid artery (ICA) increases Aβ deposition in the affected cerebral hemisphere and that correction of cerebral hypoperfusion after carotid endarterectomy (CEA) in such patients reduces Aβ deposition. Four patients with cerebral hemispheric hypoperfusion due to unilateral ICA stenosis (≥80%) and without episodes of carotid territory ischemic symptoms or infarcts in the bilateral cerebral hemispheres underwent brain perfusion single-photon emission computed tomography (SPECT) and Aβ deposition positron emission tomography (PET) with (18)F-florbetapir before and after CEA. The asymmetry ratio of the radioactive counts in the affected cerebral hemisphere relative to that in the contralateral cerebral hemisphere was calculated on SPECT and PET images. In all four patients, the SPECT-perfusion asymmetry ratio was ≤0.81 before surgery and ≥0.90 after surgery. The PET-Aβ deposition asymmetry ratio ranged from 0.98 to 1.01 before surgery. The value in two patients remained at ≥0.97 after surgery, and in the other two patients, the value decreased to ≤0.91 after surgery. These findings suggested that chronic cerebral hypoperfusion due to severe atherosclerotic stenosis of the ICA does not increase Aβ deposition in the affected cerebral hemisphere, but correction of cerebral hypoperfusion after CEA often reduces Aβ deposition.